Photoreactive UV-Crosslinkable Pressure-Sensitive Adhesives Based on Butyl Acrylate and 4-Acryloyloxy Benzophenone Copolymers - Czech, Zbigniew; Kowalczyk, Agnieszka; Kowalska, Jagoda (Journal of Research Updates in Polymer Science, 2013)
It has been previously shown that copolymers synthesized from n-butyl acrylate and unsaturated photoinitiator 4-acryloyloxy benzophenone can be used as pressure-sensitive adhesives (PSA). This paper presents synthesis and application of solvent-borne copolymer system for the preparation of photoreactive UV-crosslinkable acrylic pressure-sensitive adhesives comprising n-butyl acrylate/ benzophenone copolymers, characterized by molecular mass in the range of 180 000 to 480 000 Dalton. These copolymers were tacky but possessed insufficient cohesive strength after UV-crosslinking to be useful as PSA. They resulted in materials having a balance of cohesive and adhesive characteristics required of good PSA. Some of the parameters affecting the pressure-sensitive adhesive properties of the copolymer are: amount of the 4-acryloyloxy benzophenone, molecular mass of the polymeric components, UV-reactivity and properties, such as tack, peel adhesion and shear strength.